Neuroepithelial Bodies of Pulmonary Airways Serve as a Reservoir of Progenitor Cells Capable of Epithelial Regeneration - Reynolds, Susan D. (American Society for Investigative Pathology, 2000)
Remodeling of the conducting airway epithelium is a common finding in the chronically injured lung and has been associated with increased risk for developing lung cancer. Pulmonary neuroendocrine cells and clusters of these cells termed neuroepithelial bodies (NEBs) play a central role in each of these processes. We previously developed an adult mouse model of airway injury and repair in which epithelial regeneration after naphthalene-induced Clara cell ablation occurred preferentially at airway branch points and gave rise to nascent Clara cells. Continued repair was accompanied by NEB hyperplasia. We now provide the following evidence that the NEB microenvironment serves as a source of airway progenitor cells that contribute to focal regeneration of the airway epithelium: 1) nascent Clara cells and NEBs localize to the same spatial domain; 2) within NEB, both Clara cell secretory protein- and calcitonin gene-related peptide-immunopositive cells are proliferative; 3) the NEB microenvironment of both the steady-state and repairing lung includes cells that are dually immunopositive for Clara cell secretory protein and calcitonin gene-related peptide, which were previously identified only within the embryonic lung; and 4) NEBs harbor variant Clara cells deficient in cytochrome P450 2F2-immunoreactive protein. These data suggest that the NEB microenvironment is a reservoir of pollutant-resistant progenitor cells responsive to depletion of an abundant airway progenitor such as the Clara cell.